Towards an actionable One Health approach - Xiao-Xi Zhang; Zohar Lederman; Le-Fei Han; Janna M. Schurer; Li-Hua Xiao; Zhi-Bing Zhang; Qiu-Lan Chen; Dirk Pfeiffer; Michael P. Ward; Banchob Sripa; Sarah Gabriël; Kuldeep Dhama; et al. (BMC, 2024)
Abstract Background Despite the increasing focus on strengthening One Health capacity building on global level, challenges remain in devising and implementing real-world interventions particularly in the Asia-Pacific region. Recognizing these gaps, the One Health Action Commission (OHAC) was established as an academic community for One Health action with an emphasis on research agenda setting to identify actions for highest impact. Main text This viewpoint describes the agenda of, and motivation for, the recently formed OHAC. Recognizing the urgent need for evidence to support the formulation of necessary action plans, OHAC advocates the adoption of both bottom-up and top-down approaches to identify the current gaps in combating zoonoses, antimicrobial resistance, addressing food safety, and to enhance capacity building for context-sensitive One Health implementation. Conclusions By promoting broader engagement and connection of multidisciplinary stakeholders, OHAC envisions a collaborative global platform for the generation of innovative One Health knowledge, distilled practical experience and actionable policy advice, guided by strong ethical principles of One Health. Graphical Abstract